Management of lithium dosing around delivery: An observational study. (30th June 2020) - Molenaar, Nina M.; Poels, Eline M. P.; Robakis, Thalia; Wesseloo, Richard; Bergink, Veerle
Abstract: Objectives: Recommendations on lithium dosing around delivery vary, with several guidelines suggesting that lithium should be discontinued prior to delivery. We aimed to evaluate the validity of these recommendations by investigating 1) maternal lithium blood level changes following delivery, and 2) the association between neonatal lithium blood levels at delivery and neonatal outcomes. Methods: In this retrospective observational cohort study, we included women with at least one lithium blood level measurement during the final week of pregnancy and the first postpartum week. For aim 2, we included a subcohort of women with neonates for whom neonatal lithium blood levels (obtained from the umbilical cord or a neonatal vein puncture within 24 hours of delivery) were available. Results: There were a total of 233 maternal lithium blood level measurements; 55 (23.6%) in the week before delivery and 178 (76.4%) in the week after. There was no association between time and lithium blood level/dose ratio (Pearson correlation coefficient −0.03, P = .63). Additionally, we included a total of 29 neonates for whom a lithium measurement was performed within 24 hours postpartum. Maternal and neonatal lithium blood levels were strongly correlated. We observed no associations between neonatal lithium blood levels at delivery and neonatal outcomes. Conclusion: Based on our findings, we do not recommend lowering the dosage or discontinuation of lithium prior to delivery. Stable dosing can prevent subtherapeutic lithium serum levels, which is especially important in the postpartum period when relapse risks are highest.